2014
DOI: 10.1210/en.2013-2057
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Induces Hypothalamic Modifications Resulting in Low Feeding Efficiency, Low Body Mass and Overeating

Abstract: Intermittent fasting (IF) is an often-used intervention to decrease body mass. In male Sprague-Dawley rats, 24 hour cycles of IF result in light caloric restriction, reduced body mass gain, and significant decreases in the efficiency of energy conversion. Here, we study the metabolic effects of IF in order to uncover mechanisms involved in this lower energy conversion efficiency. After 3 weeks, IF animals displayed overeating during fed periods and lower body mass, accompanied by alterations in energy-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 60 publications
1
27
2
10
Order By: Relevance
“…Martin 2 postulated that it is unclear if the effect of calorie restriction in SPA is its reduction. Indeed, some authors confirm this statement 10,11,12,13 and others found the inverse outcome 14,15,16,17 . Such different statements are certainly also due to the employment of distinct protocols for calorie restriction with different durations.…”
Section: Introductionmentioning
confidence: 82%
“…Martin 2 postulated that it is unclear if the effect of calorie restriction in SPA is its reduction. Indeed, some authors confirm this statement 10,11,12,13 and others found the inverse outcome 14,15,16,17 . Such different statements are certainly also due to the employment of distinct protocols for calorie restriction with different durations.…”
Section: Introductionmentioning
confidence: 82%
“…Keywords: Aerobic Exercise; Endurance Training; Fat Metabolism; Thermogenesis; Fasted Exercise; D r a f t INTRODUCTION Intermittent fasting protocol (IFP), a changing in feeding periods characterized by fasting and feeding cycles, has been suggested as a strategy to change body metabolism and improve health (Horne et al 2015;Tinsley and La Bounty 2015). Many potential beneficial phenotypes are associated with IFP, such as improvements in body weight and energy expenditure (Halberg et al 2005), blood lipid profile (Benli Aksungar et al 2005), heart function (Ahmet et al 2005), eating behavior (Chausse et al 2014), trophic factors and cognitive ability (Halagappa et al 2007;Li et al 2013). Mechanistically, IFP seems to reduce body weight and increase energy expenditure by activating brown adipose tissue (BAT) nonshivering thermogenesis as well as browning of white adipose tissue (WAT).…”
Section: Effects Of Intermitent Fasting and Chronic Swimming Exercisementioning
confidence: 99%
“…The study of Chausse et al (2014), has showed that intermittent fasting alters the metabolic pattern of rats, and modifies the food consumption and hypothalamic parameters of hunger control, which results in lower feeding efficiency and overeating. The authors discuss that these alterations may be caused by overexpression of neuropeptide Y, due to the diet.…”
Section: Body Mass Feed Efficiency and Food Consumptionmentioning
confidence: 99%
“…Of note, Vega and colleagues also demonstrated that an intermittent fasting (IF) regimen, where mice had access to food every other day, reduced IL-1β and TNF levels, increased IL-6 levels, but had no effect on IL-10 following LPS (Vega et al , 2004). Although IF regimens and CR are known to result in similar weight changes, approximately 70% of ad libitum controls for 3 weeks of an IF regimen (Chausse et al , 2014) or 3 weeks of 50% CR regimen (Levay et al , 2007), it is likely that these different dietary conditions result in subtle differences in the immune response.…”
Section: Dietary Influences On Immune Function In Adulthood: Calorie mentioning
confidence: 99%